Drinking Water Supply and Agricultural Pollution : Preventive Action by the Water Supply Sector in the European Union and the United States - Schrama, Geerten J. I. (Environment & policy, 1998)
Agricultural pollution (with nitrates and pesticides) is one of the biggest threats to drinking water resources. At many places regional and local water authorities, together with the water supply industry, are involved in preventive action aimed at farming practices. Three national case studies (Germany, The Netherlands, and the United Kingdom) analyse these efforts within the context of problematical national agricultural policy and the need to implement EU directives on water quality. Additional case studies cover the role of the European Union, while the same problem in a different setting is analysed for the United States. The central question of how national and European governments can reinforce the control capacity of the actors at the regional and local level, is treated from the theoretical perspective of the policy network approach.